Engineered cell-free scaffold with two-stage delivery of miRNA-26a for bone repair - Paquet, Joseph; Moya, Adrien; Bensidhoum, Morad; Petite, Hervé (Annals of Translational Medicine; Vol 4, No 10 (May 25, 2016): Annals of Translational Medicine (Focus on “State of the Art in Diagnostics of the Acute Coronary Syndrome”), 2016)
The treatment of non-unions and bone defects is a major challenge. In these situations, autologous bone is the preferred treatment but has several serious limitations. Treatment alternatives including the use of calcium-based scaffolds alone or associated with either growth factors or stem cells have therefore been developed, or are under development, to overcome these shortcomings. Each of these are, however, associated with their own drawbacks, such as the lack of sustained/controlled delivery system for growth factors and poor cell survival and engraftment for stem cells. MicroRNAs (miRNAs), a class of small noncoding RNAs fine-tune the expression of as much as 30% of all mammalian protein-encoding genes. For instance, miRNA26a is able to promote the repair of critical-size calvarial bone defects. Yet, the clinical application of these fascinating molecules has been hampered by a lack of appropriate delivery systems. In an elegant report entitled cell-free 3D scaffold with two-stage delivery of miRNA-26a to regenerate critical-sized bone defects, Zhang et al. 2016, developped a non viral vector with high affinity to miR-26a that ensured its efficient delivery in bone defects. Engineered scaffolds were able to induce the regeneration of calvarial bone defects in healthy and osteoporotic mice. Taken together, these data pave the way for the development of advanced bone substitutes that at least will match, and preferably supersede, the clinical efficiency of autologous bone grafts. However, the transfer from the bench to the bedside of such scaffolds requires further investigations including (I) a better understanding of the underlying biological mechanisms involved in bone formation via miRNA26a; (II) evidences of polymer scaffold biocompatibility upon its complete degradation; and (III) demonstration of the engineered scaffold functionality in defects of clinically relevant volume.